Body Mass Index (BMI) Status and Associated Lifestyle Factors among Nursing Students in Universiti Malaysia Sabah - Soong, Shui Fun; Segaran Ramodran; Chyretta Burno; Mohd Ishkandar Nazlan; Wihelmina Michael (Malaysian Journal of Medicine and Health Sciences, 2020)
The Ministry of Health Malaysia over the last 20 years has initiated healthy lifestyle campaign to curb obesity but the issue has remained an escalating problem affecting Malaysians. Obesity among students in higher institute is a concern. Undergraduate student nurses as role-model advocating health, being overweight can be a problem. This study is to identify BMI status and determine associated lifestyle factors among undergraduate nurses in UMS. Methods: The study deployed a cross-sectional descriptive survey using a questionnaire to empirically asses BMI status and associated dietary and exercise practice among student nurses. Ethical clearance for the study was ob¬tained from UMS`s REC and as well as respondents` consent. A total of 100(N) nursing students were selected through stratified sampling by year of study (year 1, n=35; year 2 n=35; and year 3 n=30). Random sampling for each year of study was done using full name list generated using Microsoft excel. The study tool consists of a validated instrument which captured the respondent’s demographics, BMI index, Healthy Eating Practice Index, and Exercise Practice Inventory. Results: Among the 100 student nurses in this study, 28 students had BMI index of more than 24.9 (either being overweight, obesity Type I or Type II). Students from finalYear 3are significantly overweight(p=0.03) compared to Year 1 or Year 2 students. Comparing respondents with optimum BMI and non-optimum BMI, students who are overweight had significantly poorer Healthy Eating Practice scores and poorer Exercise practice scores. Conclusion: Findings from this study imply that 1 in 4 nursing students are overweight mostly related to poor lifestyle habits. These findings raise the rhetoric and implication of overweight nurses as health care role -models and this paper will discuss some suggestions to address the issue.